2012
DOI: 10.1038/cmi.2012.55
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in the regulation of TLR and RIG-I pathways

Abstract: The innate immune system recognizes invading pathogens through germline-encoded pattern recognition receptors (PRRs), which elicit innate antimicrobial and inflammatory responses and initiate adaptive immunity to control or eliminate infection. Toll-like receptors (TLRs) and retinoic acid-inducible gene I (RIG-I) are the key innate immune PRRs and are tightly regulated by elaborate mechanisms to ensure a beneficial outcome in response to foreign invaders. Although much of the focus in the literature has been o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
108
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(116 citation statements)
references
References 132 publications
(147 reference statements)
1
108
0
Order By: Relevance
“…However, the accumulated studies have revealed that miR-146a can induce the resistance to type I IFN by targeting STAT1, 25,27 and downregulate type I IFN expression by targeting IRAK1 and TRAF6. 43 Here, we also observed that STAT3 blockage upregulated STAT1 and TRAF6, as well as the downstream genes of type I IFN pathway. And type I IFN, which is critical for NK cell activation by blocking STAT3 in HCC cells, 4 could be increased by miR-146a inhibition accompanied with reversing HCC-mediated inhibitory effects on NK cells.…”
Section: Discussionsupporting
confidence: 54%
“…However, the accumulated studies have revealed that miR-146a can induce the resistance to type I IFN by targeting STAT1, 25,27 and downregulate type I IFN expression by targeting IRAK1 and TRAF6. 43 Here, we also observed that STAT3 blockage upregulated STAT1 and TRAF6, as well as the downstream genes of type I IFN pathway. And type I IFN, which is critical for NK cell activation by blocking STAT3 in HCC cells, 4 could be increased by miR-146a inhibition accompanied with reversing HCC-mediated inhibitory effects on NK cells.…”
Section: Discussionsupporting
confidence: 54%
“…Many proteins are known to modify the RIG-I pathway and the subsequent cytokine signal transduction (34,51,57,58), but the role of miRNA-mediated regulation is only beginning to emerge. Thus, the level of receptor expression is the first and likely effective point at which miRNAs exert their functions, but few studies have focused on the regulation of RIG-I expression by miRNAs (18). In this study, JEV infection induced miR-15b expression, and miR-15b increased JEV-induced expression of RIG-I, coincident with enhanced IRF3 signaling and NF-kB signaling, by targeting a regulon of RIG-I, RNF125.…”
Section: Discussionmentioning
confidence: 80%
“…Following JEV invasion, glial cells play an essential role in the immune response against pathogens; however, viral replication within glial cells leads to bystander neuronal death by secretion of inflammatory mediators (6). miRNAs have emerged as a major class of gene-expression regulators implicated in the immune response during inflammation and/or infections (17,18). Thus, in this study, we aimed to address the role of miRNA-regulated pathways in the JEV-induced neuroinflammation model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miRNAs have been identified as important regulators of immune responses (7) and as fine-tuners of TLRs (8). Multiple molecules involved in the TLR pathway are thought to be targeted by miRNAs, such as the expression of the TLRs themselves, TLR signal molecules, TLR-induced transcription factors, regulators of the TLR signaling pathway, and even the final functional cytokines involved in TLR signaling (9).…”
mentioning
confidence: 99%